Ring opening polymerization of dilactide using salen complex as catalyst - Idage, Bhaskar B.; Idage, Susheela B.; Kasegaonkar, A. S.; Jadhav, R. V. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
The recent concerns about our environment have led to search for environmentally benign and sustainable materials that could substitute the more commonly used petroleum based materials. Biodegradable and sustainable polylactide (PLA) is becoming one of the most promising and practical materials as a partial replacement for the petroleum-based materials. The commercially available PLA is generally homochiral poly(L-lactide) (PLLA) at present because L-lactic acid with high optical purity can only be obtained in bulk by fermentation of carbohydrate. PLLA is mostly synthesized by ring opening polymerization (ROP) of homochiral L-lactide (LLA), which is a cyclic dimer of L-lactic acid. In the present work, poly(L-lactide)s were synthesized by the ring opening polymerization (ROP) of L-lactide using iron and manganese salen complexes as catalyst. The new iron and manganese salen complexes were synthesized, purified, characterized and used as catalyst for polymerization of L-lactide. The poly(L-lactide)s prepared were characterized by infrared, proton NMR spectroscopy, solution viscosity, gel permeation chromatography, thermal analysis and X-ray diffraction. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Gel permeation chromatography; Iron salen catalyst; L-Lactic acid; L-Lactide; Manganese salen catalyst; Poly(L-lactide); ring opening polymerization; Solution viscosity